(untitled) (Acta Polytechnica CTU Proceedings, 2023)
The construction industry is one of the main sources of greenhouse gas emissions, and portland cement production is responsible for approximately 8 % of anthropogenic CO2 emissions. Microbially induced calcium precipitation (MICP) has the potential to partially replace cement or modify the properties of materials that would otherwise not find use in construction, for example, in concrete recycling. MICP might be an environmentally friendly method to improve the properties of recycled aggregates and form conglomerates from the finest fractions. In this paper, factors influencing MICP’s ability to solidify recycled concrete fines are thoroughly investigated. Calcium carbonate precipitate crystals produced by the bacterium Sporosarcina pasteurii were analyzed using scanning electron microscopy and energy dispersive spectroscopy.